Retrospective study of oxaliplatin, leucovarin and 5 fluoruracil regimen in patients with advanced gastric cancer with poor performance status: A study at a tertiary center of South India - Guruprasad, Bhat (South Asian Journal of Cancer, 2018)
Background: Gastric carcinoma is the leading cause of cancer in south India. Gastric cancer is frequently diagnosed in locally advanced or metastatic setting in Indian scenario and has a poor survival. There is no standard chemotherapy regimen which can be used in advanced gastric cancer (AGC) patients. Objective: The aim of this study was to assess the clinical activity and toxicity of oxaliplatin with infusional 5-fluorouracil and leucovorin administered every 3 weeks in patients with locally advanced and inoperable gastric cancer. Patients and Methods: In this retrospective study, the case records of 25 patients who have received OLF regimen were analyzed. Results: The median number of cycles for patients was 6 (range: 4–12 cycles). Overall response rate was 36%, with all patients having stable disease. Median survival of patients was 6 months (7 months in locally advanced). Compared to other regimens, there was less toxicity (less hematologic toxicity, less nausea and vomiting, no hair loss, no renal toxicity, no hand foot syndrome, and lesser admissions). Conclusions: OLF regimen is an acceptable regimen in poor performance status AGC patients with adequate response and an acceptable toxicity profile.
Keywords: Gastric cancer; India; OLF regimen